2020
DOI: 10.1038/s41598-020-74021-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex coherent anti-Stokes Raman scattering microspectroscopy detection of lipid droplets in cancer cells expressing TrkB

Abstract: For many years, scientists have been looking for specific biomarkers associated with cancer cells for diagnosis purposes. These biomarkers mainly consist of proteins located at the cell surface (e.g. the TrkB receptor) whose activation is associated with specific metabolic modifications. Identification of these metabolic changes usually requires cell fixation and specific dye staining. MCARS microspectroscopy is a label-free, non-toxic, and minimally invasive method allowing to perform analyses of live cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Apart from the acquisition of overview images, CARS can be applied to identify locations of lipid droplets at a higher spatial resolution. Recently, Guerenne-Del Ben et al associated the increased expression level of Tropomyosin receptor kinase B (TrkB), a specific biomarker in the progression of CRC, with increased lipid droplet signals visible in CARS images [ 111 ]. They utilized three different CRC cell lines representing stages 1 to 3 of cancer progression and expressing different levels of TrkB.…”
Section: Cellular and Tissue Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the acquisition of overview images, CARS can be applied to identify locations of lipid droplets at a higher spatial resolution. Recently, Guerenne-Del Ben et al associated the increased expression level of Tropomyosin receptor kinase B (TrkB), a specific biomarker in the progression of CRC, with increased lipid droplet signals visible in CARS images [ 111 ]. They utilized three different CRC cell lines representing stages 1 to 3 of cancer progression and expressing different levels of TrkB.…”
Section: Cellular and Tissue Diagnosticsmentioning
confidence: 99%
“…With CARS, cells were mapped at 2850 cm −1 and 2930 cm −1 , representative for CH 2 and CH 3 , respectively. Lipid droplets were visible as punctiform structures and could be associated with the cancer stage and progression of the cancer [ 111 ]. This result matched with studies by Geng et al who showed significantly higher quantities of lipid droplets in high grade CRC and glioblastoma compared to low grade cancers and healthy normal tissue [ 112 ].…”
Section: Cellular and Tissue Diagnosticsmentioning
confidence: 99%
“…Today, MCARS microspectroscopy using a dual-output sub-nanosecond laser source is recognized as a mature and straightforward technology for bioimaging, offering the high spectral resolution of conventional Raman spectroscopy with reduced acquisition time ( Kano et al, 2019 ; Kaneta et al, 2021 ). We have recently demonstrated its efficiency for cell cycle studies ( Guerenne-Del Ben et al, 2019 ) or cancer cells characterization ( Guerenne-Del Ben et al, 2020 ). In the proposed study, we naturally combine the potential of both this imaging technique and the MCR source separation method under the classical signal non-negativity constraint and, even more originally, under a new spatial constraint based on cell segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…This comparison allows us to assess the robustness of our approach by considering two very different cell types. To evaluate its applicability over a broader range, we then study HEK293 cells in different physiological states and experimental situations ( Guerenne-Del Ben et al, 2019 ; Guerenne-Del Ben et al, 2020 ). For this purpose, we compare the results of the reference (interphasic) cell to those obtained from another cell in mitosis (prophase), during which important nuclear and cytoplasmic rearrangements occur.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, not many studies have been published covering nonlinear Raman techniques ( Figure 2 A), but there is undoubtedly interest in this area of research, which is evidenced by the successful application of CARS for the label-free visualization of lipid, protein, and nucleic acid distribution in cells [ 60 , 62 ]; pigments in living cells [ 63 ]; and skin tissues [ 64 ]. The CARS technique is of particular importance in the field of cancer cell identification and diagnosis research [ 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%